Clinical and Pathologic Differences Between BRCA1-, BRCA2-, and Non-BRCA-Associated Breast Cancers in a Multiracial Developing Country - Yip, Cheng-Har; Taib, N. A.; Choo, W. Y.; Rampal, S.; Thong, M. K.; Teo, S. H. (World journal of surgery, 2009)
Background Mutations in BRCA1 and BRCA2 confer an increased risk to breast and other cancers, but to date there have only been limited numbers of studies of BRCA1- and BRCA2 -associated cancers among Asians. Malaysia is a multiracial country with three main races: Malays, Chinese, Indians. We determined whether tumor pathologic features and clinical features differ in patients with and without BRCA mutations in this Asian population. Methods We conducted a retrospective review of the medical records of 152 women with breast cancer who underwent genetic testing for BRCA mutations. The patients self-reported ethnicity, age at onset, and clinical stage at diagnosis and tumor pathology were reviewed. Results A total of 31 patients carried germline deleterious mutations (16 BRCA1 , 15 BRCA2 ). We found that tumors in BRCA1 carriers were more likely to be estrogen receptor (ER)-negative and progesterone receptor (PR)-negative. HER2 was more likely to be negative in both BRCA1 and BRCA2 subjects compared with non-BRCA subjects. We found a strong association between triple-negative status and BRCA1 carriers. In addition, tumors in BRCA1 carriers were more likely to be higher grade than those in BRCA2 and non- BRCA carriers; but the difference was not statistically significant. Conclusions These results suggest that tumors associated with BRCA1 mutations are distinct from those of BRCA2 -associated and non-BRCA-associated breast cancers, and that the tumors associated with BRCA2 mutations are similar to the non- BRCA -associated breast cancers. Further studies are required to determine if the prognosis is different in each of these groups and the best management strategy for each group.